2006
DOI: 10.1002/jor.20234
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cigarette smoking on early medial collateral ligament healing in a mouse model

Abstract: Cigarette smoking delays the healing process and increases morbidity associated with many common musculoskeletal disorders such as medial collateral ligament (MCL) injury. In the current study, a murine model of MCL healing was used to test the hypothesis that smoking impairs extracellular matrix synthesis after injury. Mice were divided into two groups, a nonsmoking control group and a group exposed to smoke for 2 months prior to surgical MCL injury. Mice were euthanized at 3 and 7 days after surgery. Subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 30 publications
0
26
0
4
Order By: Relevance
“…A potential reason is that the ''poor'' biomechanics predispose the lower limb to elevated stresses through traction and/or tibia torsion. Smoking, by delaying tissue repair [27,28], may allow these stresses to have a more detrimental on the tissues of the smoker's body.…”
Section: Discussionmentioning
confidence: 99%
“…A potential reason is that the ''poor'' biomechanics predispose the lower limb to elevated stresses through traction and/or tibia torsion. Smoking, by delaying tissue repair [27,28], may allow these stresses to have a more detrimental on the tissues of the smoker's body.…”
Section: Discussionmentioning
confidence: 99%
“…In our specialty, smoking has been associated with a delay in consolidation of fractures and injuries healing, including those involving ligaments [21]. However, there is little literature on smoking and ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking has been proven to be a preventable risk factor associated with several health conditions, such as chronic lung disease, cardiovascular disease, malignancy and low back pain [11] . Our study demonstrated that participants who currently smoked had about 7 times the risk for shoulder impingement syndrome of nonsmokers.…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated that participants who currently smoked had about 7 times the risk for shoulder impingement syndrome of nonsmokers. This could be related to the fact that nicotine can affect sensory thresholds, impair vasculature to tendons and disturb tendon healing capacity [11,12] . This tends to be con-firmed by the fact that participants who had previously smoked but had quit prior to the study had essentially the same risk as nonsmokers.…”
Section: Discussionmentioning
confidence: 99%